The illusion of limitlessness Engaging Cornel du Toit’s perspective on transhumanism and being - Igboin, Benson Ohihon (2025)
This article, in honour of Cornel du Toit, examines his scholarship, broadly in relation to science and religion, but particularly zeroes in on his idea of the nature of transhumanism and being and implications for religion. In his article titled Artificial intelligence and the question of being , Du Toit raises pluri-significant concerns regarding the emergence of superintelligent machines, capable of human-like and even superior intelligence. He explores the implications of this development for human existence, as it shifts the role of humans from being subjects to objects, with artificial intelligence taking precedence. Despite this, he concludes that there is nothing to fear about the superintelligent machines as they cannot replace human beings. This article analysed Du Toit’s arguments and concedes with him that religion has its place even in a supposedly ultra-techno-deterministic world. It does this by deploying the theory of incompleteness and mobility - that both humans and technology are incomplete in themselves, and evolving. Intradisciplinary and interdisciplinary implication: This article contributes to the debate on the relationship between religion and science and grounds it on the premise that they are not only complementary but also their agonistic differences can be meshed through the understanding of the nature of being and incompleteness.
Keywords: Cornel du Toit; Being; Illusion; Science and religion; Transhumanism